Estudo do impacto da primazia da essência sobre a forma nas demonstrações financeiras em IFRS dos cinco maiores conglomerados financeiros do Brasil - Silva, Flávia Augusta Belcorso da (2016)
With the development of globalization, it was unleashed in the Brazilian market the need for convergence of Brazilian accounting standards with international standards. This process was driven by two important factors: the foundation of the Accounting Pronouncements Committee (CPC) in 2005 and the enactment of Law 11.638/07, which brought changes concerning the preparation and disclosure of financial statements. With the internationalization of Brazilian accounting, it was highlighted a very important concept called primacy of substance over form. This conception provides greater reliability to the financial statements, since its main purpose is to represent the accounting events not only by the legal form but through, especially, the economic essence of the facts. It is important to note that the primacy of substance over form is undoing paradigms, mainly due to the fact that the Brazilian financial system comes from Roman law (code law), holding a brand of constantly influence the accounting for tax and legal aspects. However, emphasizing essence rather than merely formal aspects, the accountant has to be requested, to be attempted to more detailed analysis of the economic substance of the transaction, and provide interaction with many different company departments. Thus, with the concepts raised by the IFRS, the definition of permanent assets depreciation rate has become something much more elaborated than simply use the rates set by the tax authorities, effectively requiring the assessment of the useful life of the asset. Besides, to the business consolidation process, a more thorough evaluation of who owns the entity´s control is needed, demanding an analysis of the economic essence of participation, and to find out who owns more than 50% of the share capital of the company. Thereby, new values and several perceptions can be added to the accountant, allowing it to have a professional multidisciplinary approach to substantially review the accounting events. The present study examined the concept of the primacy of substance over form based on the investigation of various accounting pronouncements (CPC and IFRS), accounting standards issued by regulatory agencies as CVM, CFC and BCB, and bibliography of Brazilian and international notable authors. The case of Enron Corp. was also verified because it is an example of a consequence of not applying the primacy of substance over form. Ultimately, by analyzing the notes to the IFRS financial statements of the five largest financial conglomerates in Brazil – Brazil Bank, Bradesco, Itaú, Santander and Caixa Econômica Federal –, it was noted that the main impacts of the prevalence of content over formal issues are related to the non-recognition of financial assets in transactions in which there is substantial retention of risks (IAS 39, 1998), companies consolidation process (IFRS 10, 2011), rating of leases (IAS 17, 2003), and classification of hybrid instruments as liabilities or equities (IAS 32, 2005)